Natural History Dioramas: History, Construction and Educational Role - Tunnicliffe, Sue Dale (Springer, 2016)
This book brings together in a unique perspective aspects of natural history dioramas, their history, construction and rationale, interpretation and educational importance, from a number of different countries, from the west coast of the USA, across Europe to China. It describes the journey of dioramas from their inception through development to visions of their future. A complementary journey is that of visitors and their individual sense making and construction of their understanding from their own starting points, often interacting with others (e.g. teachers, peers, parents) as well as media (e.g. labels). Dioramas have been, hitherto, a rather neglected area of museum exhibits but a renaissance is beginning for them and their educational importance in contributing to people’s understanding of the natural world. This volume showcases how dioramas can reach a wide audience and increase access to biological knowledge.